Investigation of MAT2A dependency in Acute Myeloid Leukaemia: a preliminary study in Acute Myeloid Leukaemia cell line - Adão, Rita Romano Ferreira Betencourt (2018)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2017